Strategic approach through resources and servitization to a competitive organization : Aligning business operations towards unified way - Saatsi, Lenni (My University, 2025)
Global competition and rapid technological change have intensified the need for organizations to differentiate beyond cost efficiency and operational excellence. This creates the need for organizations to evaluate and adjust strategic approaches that they use and apply to create sustainable competitive advantage. If internal processes are not adjusted as the markets evolve, companies may fall behind compared its rivals especially in service-oriented solutions. This thesis aims to discover what companies need to consider when aligning different business operations as part of their servitization strategy. To find out how this is applied, this thesis combines the previous theoretical contributions of Resource-Based View and servitization to form a revised theoretical framework that show-cases the practical implications that different business operations need to consider when integrating the broader view of strategic approach of the company. Additionally, this thesis sheds the light for organizations in the context of micro-foundational aspects that are crucial for creating a unified organizational culture. This is done by conducting a qualitative case study in a multinational company called ARKANCE which provides software and services for the AEC and manufacturing industries. The primary data for this study was collected from 13 semi-structured interviews. All of these individuals are working in the case company in different roles across the EMEA region. The findings of this study reveal that successful servitization requires a lot of cross-functional collaboration and cultural adaptation throughout the organization to achieve the desired outcomes in the corporation. By addressing the issues that local entities struggle on a daily basis, the company can align its business operations across the region as part of the vision to become the partner of choice for their customers in digital transformation. In addition, the findings reveal that agile capabilities play a crucial part as the organizational structures are reforged to meet the market needs. This suggests that the alignment of different business operations entail overlapping areas of responsibility, particularly within the more in-depts dimensions of value creation. To achieve its objectives from a service business perspective, the company must ensure capability management at both individual and organizational levels. This requires identifying employees’ competencies and readiness to operate at the customer interface, as well as assessing internal resources and processes to comprehensively meet customer needs. To conclude, a systematic approach to mapping and developing capabilities establishes the foundation for high-quality service delivery and sustainable competitive advantage.

Globaali kilpailu ja nopea teknologinen kehitys ovat lisänneet tarvetta organisaatioille erottua kustannus- ja operatiivisentehokkuuden lisäksi. Tämä luo organisaatioille tarpeen arvioida ja mukauttaa strategisia lähestymistapoja, joilla pyritään saavuttamaan kannattavaa kilpailuetua. Mikäli sisäisiä prosesseja ei sopeuteta markkinoiden muuttuessa, yritykset voivat jäädä jälkeen kilpailijoistaan erityisesti palvelulähtöisten ratkaisujen tarjonnassa. Tämän tutkielman tavoitteena on selvittää, mitä yritysten tulee huomioida yhdenmukaistaessaan eri liiketoimintoja osana servitisaatiostrategiaansa. Tutkielma yhdistää resurssipohjaisen näkökulman (Resource-Based View) ja servitisaation aiemmat teoreettiset kontribuutiot muodostaakseen tarkistetun teoreettisen viitekehyksen, joka havainnollistaa käytännön vaikutuksia, joita eri liiketoimintayksiköiden on otettava huomioon integroidakseen yrityksen strateginen lähestymistapa. Lisäksi tutkielma tuo esiin mikrotaloudellisen tason merkityksen yhtenäisen organisaatiokulttuurin luomisessa. Työn empiirinen osuus toteutettiin laadullisena tapaustutkimuksena monikansallisessa yrityksessä nimeltä ARKANCE, joka tarjoaa ohjelmistoja sekä palveluita AEC- ja valmistavan teollisuuden aloille. Tutkimuksen ensisijainen aineisto kerättiin puolistruktuurisella haastattelumenetelmällä, johon osallistuneet 13 henkilöä toimivat eri rooleissa EMEA-alueella. Tulokset osoittavat, että onnistunut servitisaatio edellyttää laajaa toimintojen välistä yhteis-työtä ja kulttuurista sopeutumista koko organisaatiossa, jotta yrityksessä saavutetaan halutut tulokset. Paikallisten yksiköiden päivittäisten haasteiden ratkaiseminen mahdollistaa liike-toimintaprosessien yhdenmukaistamisen alueellisesti osana yrityksen visiota olla asiakkaidensa ensisijainen kumppani digitaalisen muutoksessa. Lisäksi tulokset korostavat ketterien kyvykkyyksien keskeisiä rooleja, kun organisaatiorakenteita muokataan vastaamaan markkinoiden tarpeisiin. Tämä viittaa siihen, että eri liiketoimintayksiköiden välinen yhden-mukaistaminen sisältää päällekkäisiä vastuualueita erityisesti arvonluonnin syvemmillä osa-alueilla. Palveluliiketoiminnan tavoitteiden saavuttamiseksi yrityksen on varmistettava kyvykkyyksien hallinta sekä yksilö- että organisaatiotasolla. Tämä edellyttää työntekijöiltä osaamista ja valmiutta toimimaan asiakasrajapinnassa sekä sisäisten resurssien ja prosessien ymmärtämistä, jotta asiakastarpeisiin voidaan vastata kokonaisvaltaisesti. Näin voidaan todeta, että systemaattinen lähestymistapa kyvykkyyksien kartoittamiseen ja kehittämiseen luo perustan korkealaatuiselle palveluliiketoiminnalle sekä kestävälle kilpailuedulle.
Keywords: business operations; strategic planning; service business; fi=Kansainvälinen liiketoiminta|en=International Business|; Master’s Programme in Strategic Business Development